2014
DOI: 10.2139/ssrn.2521399
|View full text |Cite
|
Sign up to set email alerts
|

The Elasticity of Taxable Income and Income-Shifting: What is 'Real' and What is Not?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 32 publications
(52 reference statements)
3
42
1
Order By: Relevance
“…Previous US studies show that a large proportion of the behavioral response of high‐income individuals has been in the form of tax avoidance via income‐shifting (see, e.g., Saez et al ., ). Harju and Matikka () show that a similar result holds for the owners of privately held businesses in Finland. In addition, the US studies have shown that charitable giving, which is tax‐deductible in the US, responds to changes in marginal tax rates (see, e.g., Bakija and Heim, ).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Previous US studies show that a large proportion of the behavioral response of high‐income individuals has been in the form of tax avoidance via income‐shifting (see, e.g., Saez et al ., ). Harju and Matikka () show that a similar result holds for the owners of privately held businesses in Finland. In addition, the US studies have shown that charitable giving, which is tax‐deductible in the US, responds to changes in marginal tax rates (see, e.g., Bakija and Heim, ).…”
mentioning
confidence: 69%
“…However, I do not find the ETI to be larger among high‐income earners compared with middle‐income individuals, although many previous studies have found different results. One potential explanation for this finding is that available tax avoidance opportunities are in general very limited even among high‐income earners in Finland (with the exception of the owners of privately held corporations; see Harju and Matikka, ). In contrast, the larger estimates among top income earners in the earlier studies, particularly in the US, tend to be driven by tax avoidance responses (Saez et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our paper also relates closely to the line of research cited above, which analyses the choice of remuneration regime for business owners (wages or dividends), especially the work of Harju and Matikka (). These authors analyse income shifting in a very similar way to our approach here, using the tax rate differential between wages and dividends to measure income shifting between them after the 2005 reform in Finland.…”
Section: Introductionmentioning
confidence: 76%
“…To analyse the incentives for taxpayers to decide the composition of their income based on the different taxes charged on its components, we will extend a simple static model of income shifting developed by Piketty and Saez (), Piketty, Saez and Stantcheva () and Harju and Matikka ()…”
Section: The Modelmentioning
confidence: 99%